Estudo dos condicionantes dos transtornos osteomusculares e do absenteísmo a partir de uma revisão sistemática e de um estudo de caso - Coimbra, Leonardo da Silva (2022)
Traditionally, absenteeism has been pointed out as a complex phenomenon with a multifactorial etiology within a scenario of multicausality. The health issues caused by musculoskeletal disorders reflect a dysfunction in the productive process and are one of the most common problems in the manufacturing industry, causing pain, disability and impairment of the movements of workers, all of which are directly linked to low productivity and workplace absenteeism. Given these findings, the objective of the study was to analyze the determinants of musculoskeletal disorders and absenteeism based on a systematic review and a case study. To understand this phenomenon, a systematic literature review was used using the Methodi Ordinatio, and for the case study, the multivariate Poisson regression model and cluster analysis were used. 480 workers participated in the study between the years 2019 to 2021. The absenteeism rate was 5.71% of absences. Regarding musculoskeletal disorders, it was observed that 60.6% of the ICD-M are related to back pain problems (ICD-M54), and 13.9% of the musculoskeletal problems are associated with shoulder problems (ICD-M75), with a significance value of p = 0.00. Regarding the Poisson statistical analysis between the variables, it was identified that the age group > 60 years is one of the predictors of absenteeism related to ICD-M54, with a significance value of p < 0.02. Regarding the locations, the “Sandwich Cookie” sector of Unit II stood out, with an average of 1.9 (±1.6) and a significance value of p = 0.00 days absent. In relation to night work, it has a significance value of p = 0.00 in workplace absences. Regarding vacations, it can also be pointed out that there is a relevant relationship between employees who have the lowest number of vacation days and days of absenteeism, with a value of p = 0.01. It is concluded that factors associated with a greater risk of absenteeism include the musculoskeletal condition of back pain, the age over sixty years old, and a low number of vacation days in the productive area of the food industry, with emphasis on the “Sandwich Cookie” sector of Unit II during the night shift. The results may contribute to the management of an ergonomic action plan, in addition to suggesting an increase in workplace turnover, enabling a decrease in musculoskeletal disorders, optimizing performance and promoting the health of employees.